Keanekaragaman Arthropoda pada Budidaya Padi Ratun di Kecamatan Sedayu, Kabupaten Bantul, Daerah Istimewa Yogyakarta - Prasetyo, Mahmudin Tri; Santi, Idum Satya; Tarmadja, Samsuri; Pustika, Arlyna Budi (Program Studi Agroteknologi INSTIPER, 2025)
Ratun is a rice cultivation technique, which is a rice plant that grows from the leftovers cut from rice clumps after harvesting with the aim of saving rice field management in rice cultivation. Arthropods are animals with a body characterized by a spineless and segmented body, body parts consisting of the head, chest, and abdomen which are completely wrapped by chitin and the exoskeleton. This study aims to determine the diversity of arthropods in ratun rice plants. The research was carried out in April - June 2023, and is located in Argodadi Village, Sedayu District, Bantul Regency, Special Region of Yogyakarta. The sample collection in this study was divided into several ways, namely pit fall, networking, yellow traps, and direct observation per clump. The formula used to calculate the arthropod diversity index is Shannon-Wiener and Gini-Simpson. The results of the analysis of the arthropod diversity index showed that the ratun rice had moderate diversity based on the Shannon-Wiener index, while the Gini-Simpson index showed a fairly high level of diversity